ASESMEN PERKEMBANGAN PADA ASPEK NILAI MORAL DAN AGAMA DENGAN MENGGUNAKAN TEKNIK PENILAIAN UNJUK KERJA - Syafi’i Imam; Suroyyah Ikrima (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
This study aims to describe the development of students' moral values, teacher activities, student activities, assessment techniques for work, and analyze the results of the development of students' religious and moral values. The type of research and approach in this research is descriptive qualitative research. While the research subjects consisted of teachers and students aged 4-5 years in TK-Zainuddin. Secondary data used in data collection by using instruments of observation, interviews, and documentation techniques that connect researchers to solve a problem. The results of the research were obtained in the development of moral values, religion, namely, by using performance appraisal techniques with activities including greeting, polite to older people, honest, responsible, polite when speaking every Sunday. These activities include practicing the fardhu prayer movement. Then every month they make pilgrimages, visit orphanages, and every semester holds PHBI events. In assessing performance techniques on aspects of the development of moral values, religion carried out in Zanuddin Kindergarten by teachers is to use portfolios and checklists as assessment instruments.